Cell type‐specific and subcellular expression of phospholipid phosphatase‐related proteins to modulate lyso‐phosphatidic acid synaptic signaling in the developing and adult CNS - Polyzou, Alexandra; Fuchs, Joachim; Kroon, Cristina; Kotoula, Androniki; Delis, Foteini; Turko, Paul; Antoniou, Katerina; Eickholt, Britta; Leondaritis, George (Journal of neurochemistry, 2024)
Lysophosphatidic acid (LPA) is a bioactive phospholipid that participates in critical processes in neural development and adult brain function and is implicated in various pathophysiological conditions. Along with its six well‐characterized receptors, atypical regulators of LPA signaling have also been suggested, including phospholipid phosphatase‐related proteins (PLPPRs). PLPPRs have been mostly studied in the developing brain where they control LPA‐dependent axon guidance, cortical network hyperexcitability, and glutamatergic neurotransmission. PLPPR4 and PLPPR3 represent two closely related proteins reported to localize predominantly in dendrites and axons, respectively, and differ in their developmental expression patterns. Herein, we have revised the expression patterns of PLPPRs in the cerebellum, dorsal and ventral hippocampus, prefrontal cortex (PFC), nucleus accumbens, and striatum during development and in the adult using quantitative PCR. Expression patterns of Plppr2,4 and 5 were consistent with previous studies, whereas Plppr3 and Plppr1 exhibited a unique expression profile in nucleus accumbens (NAc) and striatum in later developmental and adult stages, which we verified at the protein level for PLPPR3. To investigate neuron type‐specific expression at the single cell level, we developed a bioinformatic tool to analyze recent single‐cell RNA‐sequencing data in the cerebral cortex and hippocampus of adult mice. Our analysis revealed a widespread but also selective adult neuron‐type expression with higher expression levels of Plppr3, Plppr1, and Plppr5 in GABAergic and Plppr4 and Plppr2 in glutamatergic neurons. PLPPR4 has been identified as a post‐synaptic modulator of LPA levels in glutamatergic synapses operating via an uptake mechanism, to control LPA‐dependent cortical network hyperexcitability. Using subcellular fractionation experiments, we found that both PLPPR4 and PLPPR3 are co‐expressed in adult synaptosomal membranes. Furthermore, flow cytometry experiments in HEK293 cells showed comparable LPA uptake by PLPPR4 and PLPPR3, whereas PLPRR3, but not PLPPR4, induced also uptake of monoacylglycerol, the dephosphorylation product of LPA. We propose that synaptic LPA may be subject to both pre‐synaptic and post‐synaptic mechanisms of regulation by PLPPRs in addition to LPARs in developing and adult synapses. Lysophosphatidic acid (LPA) is a phospholipid with critical roles in the developing and adult brain. Besides typical LPA receptors, proteins such as the phospholipid phosphatase‐related PLPPRs may serve as atypical regulators of LPA functions. Here, we have investigated PLPPR expression and localization in several brain regions as well as their neuron‐type specific expression during development and in adulthood. Focusing on two prominent PLPPRs, PLPPR3 and PLPPR4, we show their co‐expression in adult synapses and their involvement in the regulation of LPA levels. Our results suggest that PLPPRs may control synaptic LPA levels by both pre‐synaptic and post‐synaptic mechanisms.